Exploring Chinese university students’ foreign language enjoyment, engagement and willingness to communicate in EFL speaking classes - Jie Lin; Yongliang Wang (Humanities & Social Sciences Communications)
Abstract Growing research attention has focused on examining the role of emotions in Second Language Acquisition (SLA), with particular emphasis on positive emotions and student engagement as significant factors in promoting various aspects of human behavior and cognition. Despite the significance of Willingness to Communicate (WTC) in understanding learners’ communicative behaviors in a foreign language, there still exist gaps in understanding how positive emotions like Foreign Language Enjoyment (FLE) and behavioral engagement relate to WTC. This study investigates the relationships among FLE, behavioral engagement, and WTC within the Chinese English as a Foreign Language (EFL) context, drawing upon the Broaden-and-Build theory. Therefore, the study examined how 690 Chinese EFL college students perceive FLE and behavioral engagement related to their WTC by using a quantitative method. The findings revealed significant positive relationships between FLE and behavioral engagement with WTC, with FLE showing a stronger association than behavioral engagement. Moreover, FLE and WTC could significantly and strongly predict WTC. These findings offer valuable insights for educational practices and policy development, suggesting the potential benefits of incorporating enjoyment-focused strategies in language learning. Additionally, this research contributes to our understanding of how positive emotions, particularly enjoyment, may work alongside other factors to enhance students’ communicative competence and overall experience in language learning.